WIEK EMERYTALNY LUDNOŚCI W PAŃSTWACH UNII EUROPEJSKIEJ W KONTEKŚCIE OBCIĄŻENIA EKONOMICZNEGO I PRZECIĘTNEGO TRWANIA ŻYCIA - Murkowski, Radosław (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2012)
The author proposes a technique of calculating the postulated minimum upper limit of the productive age, which uses potential demography methods. The technique is based on the postulate that the total number of years to live after the productive age for the whole population should not be higher than the total years to live in the productive age. This method accounts for both the length of the life expectancy and the population age structure. The minimum upper limit of the productive age is the highest for the population with a long life expectancy and high age dependency ratio. The results obtained using this technique for calculations in all European Union member states were compared and related to the statutory pension ages.